A Review of Influenza Vaccine Immunogenicity and Efficacy in HIV-Infected Adults. Issue 6 (2008) - Cooper, Curtis; Hutton, Brian; Fergusson, Dean; Mills, Edward; Klein, Marina B; Boivin, Guy; Halperin, Scott
Abstract : BACKGROUND: HIV-seropositive adults are at an increased risk for influenza infection. They also develop more severe influenza disease and are hyporesponsive to current influenza vaccinations. METHODS: The authors examined findings from a systematic review of influenza vaccination in HIV-seropositive adults, and evaluated other relevant studies. A narrative overview of findings formulated to summarize the implications of currently available literature is presented. The primary goal of the present review is to assess the limitations of current evidence and to provide a framework for additional research. RESULTS: There is a paucity of knowledge regarding the relative value of prophylactic influenza vaccination in HIV-positive adults compared with immunocompetent populations. There are shortcomings related to study methodology and temporal changes in the characteristics of patient baseline immune status, which limit the utility of this information to shape public health policy. CONCLUSIONS: There is a pressing need to pursue methodologically rigorous studies that will increase knowledge related to improving the effectiveness of preventive influenza measures in this patient population.